A Mapping and Visualization of the Role of Artificial Intelligence in Sport Industry - mohammad mohsen sadr; tahereh saheb; Abolfazl Farahani (Research in Sport Management and Marketing)
Purpose: The purpose of this study is to analyze how the scientific community has assessed and addressed the application of artificial intelligence in the sports industry and to identify dominant academic themes and neglected topics.Methods: A total of 2023 articles and 13081 keywords were analyzed for co-occurrence analysis. The analysis aimed to identify the dominant academic themes that scholars tackle and the topics that are neglected.Results: The analysis identified seven core topics, including real-time sport medicine, wearable technology, swarm intelligence, automatic motion detection and deep image analysis, intelligent athlete training and education, and athlete robots. The study also revealed the necessity for increased scholarly focus on subjects like precision sports medicine and metaverse technology.Conclusion: The revolutionary technology of artificial intelligence has impacted all industries, including the sports sector. The analysis demonstrates how AI has revolutionized the sports sector and what areas require further attention. Policy makers and the scientific community can utilize this study as a practical guide to better grasp the impact of AI on the sports industry.